Simulation of Thermal Stratification and Salinity Using the Ce-Qual-W2 Model (Case Study: Mamloo Dam) - Sabeti, R.; Jamali, S.; Jamali, H. H. (Engineering, Technology & Applied Science Research, 2017)
Due to the shortage of fresh water, the quality of stored water in reservoirs has become increasingly important. Thermal regime and salinity are factors that affect the quality of water reservoirs. These two parameters were studied in Mamloo Dam in Tehran province. This dam has recently started to be uses as a source of drinking water for Tehran and thus its water quality is of increased importance. In this regard, the hydrodynamic model for 2014 to 2015 was built and calibrated by the CE-QUAL-W2 model and the model was used to simulate the thermal regime and salinity up to 2020. Two main scenarios were studied in this period, the continuation of the current situation or a 2.5% increase in water requirements and 5% decrease in discharge. The results show that the reservoir will experience thermal stratification in the summer and vertical mixing in the winter. Dased on these results Mamloo reservoir is in branch of warm Monomictic lake. Also results showed that thermal stratification and ssalinity stratification dominates simultaneity. Besides this issue with 2.5% increase in water requirements and 5% decrease in discharge, duration of summer thermal stratification will decrease although intensity of thermal stratification will increase.